SPE International Symposium and Exhibition on Formation Damage Control 2008
DOI: 10.2118/112397-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Chemical Sand Consolidation as a Remedial Sand-Control Option on the Heidrun Field

Abstract: The Heidrun field located in the Norwegian Sea is an oil and gas producing field which has been developed with a tension leg platform (TLP) installed over a template with 56 slots. Two subsea production templates and three subsea water injection templates are also tied back to the TLP. All wells require sand control measures in the reservoir section to prevent sand production. The sand control philosophy has gradually evolved from cased hole gravel packs, through stand alone screens to todays preferred option … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…More detailed information on these results will be reported elsewhere [13]. Unfortunately, this test could only be effectuated 80 days after the initial back production and the well had been producing on and off during this period.…”
Section: Case Historymentioning
confidence: 97%
“…More detailed information on these results will be reported elsewhere [13]. Unfortunately, this test could only be effectuated 80 days after the initial back production and the well had been producing on and off during this period.…”
Section: Case Historymentioning
confidence: 97%
“…Chemical sand consolidation technology prior to a squeeze has been done as a means of reducing the risk for sand production after a squeeze operation (Haavind et al, 2008).…”
Section: Formation Damagementioning
confidence: 99%
“…Haavind et al, (2008) reported that well A-14 was treated 3 times over a period of 14 months with sand consolidation chemical prior to scale squeezes. Water based scale inhibitor squeezes have also started sand production in some wells on Heidrun.…”
Section: Viscosified Inhibitor Formation Damagementioning
confidence: 99%
“…orientation and diameter of the perforations [26], [8] , inclination and azimuth of the well) or by shooting the perforations only in the layers with best mechanical properties. It is also possible to complete the well with tools (such as standalone or expandable screens, gravel or frac pack or chemical consolidation [9] ) which prevent the sand particles, once detached from the formation, to be dragged into the well by the fluid flow.…”
Section: Introductionmentioning
confidence: 99%